Osteogenesis Imperfecta Diagnosed from Mandibular and Lower Limb Fractures: A Case Report. Issue 2 (June 2016) - Kobayashi, Yoshikazu; Satoh, Koji; Mizutani, Hideki
Osteogenesis imperfecta (OI) is a congenital disease characterized by bone fragility and low bone mass. Despite the variety of its manifestation and severity, facial fractures occur very infrequently. Here, we report a case of an infant diagnosed with OI after mandibular and lower limb fractures. A boy aged 1 year and 3 months was brought to his neighboring hospital with a complaint of facial injury. He was transferred to our hospital to undergo operation 3 days later. Computed tomography images revealed multiple mandibular fractures including complete fracture in the symphysis and dislocated condylar fracture on the right side. Open reduction and internal fixation with absorbable implants was performed 7 days after injury. He fractured his right lower limb 2 months later. He was diagnosed with OI type IA by an orthopedist. He will be administered bone-modifying agents if he suffers from frequent fractures.